Cells immunoreactive for neuropeptide in human thymomas. Issue 10 (October 1990) - Lauriola, L; Maggiano, N; Larocca, L M; Ranelletti, F O; Ricci, R; Piantelli, M; Capelli, A
Abstract : The presence of opioid peptides, bombesin, and substance P was investigated by immunohistochemistry in tissue sections from six human thymomas. The number of immunoreactive cells seemed to vary from one case to another. Ultrastructural investigation, showing the presence of desmosomes in labelled cells, allowed these cells to be classified as epithelial lineage cells. The occurrence of cells containing neuropeptide in thymomas suggest that peptide molecules could have modulated the behaviour of this tumour, given the reported influence of these molecules on immune functions and their growth promoting activity on several cell types, including mesenchymal and epithelial cells.